PENGGUNAAN KONSEP DASAR ASESMEN PSIKOLOGIS DALAM PENDIDIKAN - Ami Putri Nadia; Looeziana Ucee (CV. ADIBA AISHA AMIRA, 2025)
Psychological assessment in education is a process to determine the psychological state of students, support diagnosis, and design appropriate interventions. The basic concepts of psychological assessment include various theories from figures such as Carl Rogers, who emphasized the importance of individuals' subjective experiences in assessment, and Raymond Cattell, who developed a psychological model based on factor analysis to measure dimensions of intelligence and personality. In Indonesia, educational assessment underwent a significant transformation, especially with the implementation of Curriculum 2013, which focuses on higher-order thinking skills and the all-round development of students' abilities. This change is also reflected in the introduction of the National Assessment (AN), which replaces the National Exam (UN) and aims to assess students' literacy, numeracy and character. Assessment is no longer just an evaluation of academic achievement, but a tool that supports the continuous learning process. The assessment methods used, such as formative and summative assessments, provide constructive feedback to improve and optimize learning. In addition, national assessments provide a broader picture of the quality of education in Indonesia. This assessment approach includes various instruments, such as written tests, oral tests, observations, interviews and portfolios, which aim to evaluate students' social, emotional and academic dimensions